Drug repurposing: A novel strategy to target cancer stem cells and therapeutic resistance - Divya Ajmeera; Rajanna Ajumeera (Genes and Diseases, 2024)
Chemotherapy is an effortless and frequently used approach in cancer therapy. However, in most cases, it can only prolong life expectancy and does not guarantee a complete cure. Furthermore, chemotherapy is associated with severe adverse effects, one of the major complications of effective cancer therapy. In addition, newly published research outputs show that cancer stem cells are involved in cancer disease progression, drug resistance, metastasis, and recurrence and that they are functional in the trans-differentiation capacity of cancer stem cells to cancer cells in response to treatments. Novel strategies are therefore required for better management of cancer therapy. The prime approach would be to synthesize and develop novel drugs that need extensive resources, time, and endurance to be brought into therapeutic use. The subsequent approach would be to screen the anti-cancer activity of available non-cancerous drugs. This concept of repurposing non-cancer drugs as an alternative to current cancer therapy has become popular in recent years because using existing anticancer drugs has several adverse effects. Micronutrients have also been investigated for cancer therapy due to their significant anti-cancer effects with negligible or no side effects and availability in food sources. In this paper, we discuss an ideal hypothesis for screening available non-cancerous drugs with anticancer activity, with a focus on cancer stem cells and their clinical application for cancer treatment. Further, drug repurposing and the combination of micronutrients that can target both cancers and cancer stem cells may result in a better therapeutic approach leading to maximum tumor growth control.